2015
DOI: 10.1038/srep14606
|View full text |Cite
|
Sign up to set email alerts
|

Dairy products consumption and metabolic syndrome in adults: systematic review and meta-analysis of observational studies

Abstract: The association of dairy products consumption with risk of metabolic syndrome (MetS) has been inconsistently reported in observational studies. A systematic review and meta-analysis of published observational studies was conducted to quantitatively evaluate this association. Relevant studies were identified by searching PubMed and EMBASE databases and by carefully checking the bibliographies of retrieved full reports and related reviews. Eligible studies were observational studies that investigated the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 57 publications
1
43
0
1
Order By: Relevance
“…Two meta-analyses (22, 23) recently examined the association between dairy consumption and the risk of MetS. Analyses were based on data from a total of 9 individual prospective cohort studies, of which 3 used National Cholesterol Education Program–Adult Treatment Panel III MetS criteria (35, 41, 42), 1 study used National Cholesterol Education Program–Adult Treatment Panel III criteria with modified waist circumference thresholds (38), 1 study used the insulin-resistance syndrome criteria (34), 1 study used the American Heart Association criteria (43), 2 studies used the International Diabetes Federation criteria (44, 45), and 1 study used both American Heart Association and International Diabetes Federation criteria (40).…”
Section: Dairy and Cardiovascular-related Clinical Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Two meta-analyses (22, 23) recently examined the association between dairy consumption and the risk of MetS. Analyses were based on data from a total of 9 individual prospective cohort studies, of which 3 used National Cholesterol Education Program–Adult Treatment Panel III MetS criteria (35, 41, 42), 1 study used National Cholesterol Education Program–Adult Treatment Panel III criteria with modified waist circumference thresholds (38), 1 study used the insulin-resistance syndrome criteria (34), 1 study used the American Heart Association criteria (43), 2 studies used the International Diabetes Federation criteria (44, 45), and 1 study used both American Heart Association and International Diabetes Federation criteria (40).…”
Section: Dairy and Cardiovascular-related Clinical Outcomesmentioning
confidence: 99%
“…Chen et al (22) reported an inverse association between total dairy consumption and the risk of MetS (RR: 0.86; 95% CI: 0.79, 0.92; Supplemental Table 12 ). There was no heterogeneity between studies, and no evidence of publication bias.…”
Section: Dairy and Cardiovascular-related Clinical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…MetS represents a cluster of at least three metabolic risk factors including central obesity, elevated blood pressure, dysglycemia, hypertriglyceridemia, and low high‐density lipoprotein (Vassallo, Driver, & Stone, ). MetS was found to increase risk of diabetes and cardiovascular disease (Chen et al., ). Hypertension, chronic inflammation, and insulin resistance are interrelated, contributing to MetS (Lteif, Han, & Mather, ).…”
Section: The Mechanism Of Tripeptides Ipp and Vppmentioning
confidence: 99%